Quando gritô a liberdade: Identidade e território em Santo Antonio dos Sardinha - TRABULSI, Maria Tereza Nunes (2013)
This dissertation is the result of research conducted in Santo Antonio dos Sardinha, located in the municipality of Lima Campos - MA. The family groups that occupy the land of Santo Antonio have a very specific way of relating to the land and other natural resources in the territory under its control since the abandoning the lands by the old master in the late nineteenth century. There are at least 123 years they held a party in honor of the patron saint within a territory that is designated by them as terra de preto or terra de dono. The dissertation seeks to understand the process of territorialization of Santo Antonio dos Sardinha held by families, highlighting aspects that contributed not only to the delimitation of its territory, but also the identity of the ethnic group studied.